FLYPAPER EFFECT PADA DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Aliferiana Irsyadhea Putri; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
This study aimed to elucidate the effect of General Allocation Funds (DAU) and Regional Own-source Revenue (PAD) on regional expenditures (BD) and to give empirical evidence whether flypaper effects occurs in sub-districts / cities in Central Java Province from 2013 to 2017. The population and sample consisted of 29 regencies and 6 municipalities in Central Java Province with a total of 175 observation data. The data used is secondary data in the form of audited reports Actual Budget and Expenditure. This research was tested using multiple linear analysis techniques that were processed using the SPSS application (Statistical Product and Service Solution). The results showed that the PAD and DAU simultaneously and partially have a significant effecting on regional expenditures. In addition, the results of data processing also showed higher DAU Standardized Coefficients than PAD, which proved that there was a flypaper effect.